Dough boys - Chase, Paula (Greenwillow Books, 2020)
Told in two voices, thirteen-year-old best friends Simp and Rollie play on a basketball team in their housing project, but Rollie dreams of being a drummer and Simp, to impress the gang leader, Coach Tez.